A multipath model of salesperson performance in the financial services industry. (2nd October 2017) - Varghese, Jose; Edward, Manoj; Sahadev, Sunil
Abstract : Purpose: The study looks at how salesperson's customer orientation (SCO) mediates the impact of a host of organisational, job-related and personality-related factors on salesperson performance. Previous studies that have considered the impact of customer orientation on performance have often considered a limited number of antecedent variables which has led to inconsistent results. The purpose of this paper is to address this concern by considering the multiple effects of several independent variables. Design/methodology/approach: The conceptual model was tested through a large-scale survey of financial services salespersons in India. A total of 1, 106 respondents participated in the survey. The data were analysed through structural equations modelling. Sobel's test was employed to test the mediating effects. Findings: The study found that customer orientation has a significant mediating effect in the case of several antecedent variables. The impact of variables like perceived supportive work environment, experienced meaningfulness, organisational identification, salesperson agreeableness and salesperson instability on salesperson performance is seen to be partially or fully mediated by SCO. Research limitations/implications: The cross-sectional design and the convenience sampling methodology are the main limitations of the study. Practical implications: The study develops a more holistic, multipath model which can help managers as a guideline in recruiting and selecting salespersons. The importance of customer orientation points towards the need for better attitudinal training. Originality/value: Theoretically, the paper highlights the need for developing more comprehensive models for considering the consequences of customer orientation and related issues. The multipath model addresses several calls for research on testing different antecedents of customer orientation as well as how customer orientation enhances salesperson performance.